Uma análise comportamental da inteligência : possibilidades de intervenção e diálogos com a psicometria - Rabelo, Laura Zamot (2015)
Psychometrics began with the investigation of individual differences in the 19th century. Initially, the differences were attributed to sensory acuity; however, soon they were replaced by the mental faculties. Since then, many theories, models and different types of assessment were proposed to enable a better understanding of what is called intelligence. Currently, the Cattell-Horn-Carroll intelligence model is the most widely used and includes the contributions from different theorists in the area. Behaviour Analysts did not consider intelligence an object of study because they regarded it as a mentalistic entity. Additionally, behaviour analysts criticised many crucial elements of Psychometrics such as the use of tests to assess intelligence and statistical criteria to establish behavioural criteria. However, when Stimulus Equivalence Theory and Relational Frame Theory emerged, it became possible to interpret and study language, complex behaviour and cognitive processes as stimulus relations. As correlations between relational tasks performances and the IQ were provided by different tests, Cassidy, Roche e Hayes (2011) investigated whether a relational training could enhance intellectual functioning. These authors found significant improvements in IQ in 12 year-olds following a relational training involving sameness, opposition and comparison relations. The present study replicated Cassidy et al. (2011) with 11 participants ranging from 6 to 9 years, adapting the procedure accordingly to their needs. Only one child was able to finish the training, almost one and a half years after started training. Most children improved their IQ scores; nevertheless, improvements shown by the participants from the experimental condition were equivalent to the ones presented by children from the control condition. The procedure was too complex for younger participants. Future studies should assess and train prerequisite repertoires for relational training, as well as promote alterations in the training structure. Correlation analyses between relational task performance and the intelligence assessment scores were run and results corroborated the literature. The number of sessions and stimulus sets of the contextual cue training were correlated with verbal measures from WISC-III, showing a relationship between relational repertoires and language. A preliminary behavioural interpretation of intellectual abilities described in the Cattell-Horn-Carroll model was proposed, which should be seen as first steps toward planning new relational training protocols which might contain critical features to improve cognitive functioning. Despite their relevance, terminological, theoretical and philosophical differences between Psychometrics and Behaviour Analysis were not in the centre of our analysis. The main objective was to promote a dialogue between both areas. The interchange between them may help in the planning of effective interventions, which is the ultimate goal for both of them.